Digitalization, Net-Zero Strategies, and Sustainable Economic Growth in Vietnam - Lai, Nam Tuan; Nguyen, Thi Hoa (International Journal of Energy Economics and Policy, 2025)
This study investigates the dynamic relationship between digitalization, economic sustainability, and Vietnam's pursuit of Net Zero emissions from 1975 to 2023, a period marked by rapid technological advancements. Employing econometric methods, including unit root tests, Johansen cointegration, and Granger causality, alongside robustness checks using Dynamic Factor Analysis (DFA) and Principal Component Analysis (PCA), the research explores the complex interlinkages between digital connectivity, economic sustainability indicators, and emissions. Findings reveal a statistically significant positive relationship between digitalization and emissions, acknowledging technology's dual role in both economic resilience and environmental impact. Trade intensity, private consumption, and primary sector activities, particularly energy-intensive agriculture and export-oriented industry are identified as significant drivers of CO2 emissions. The analysis quantifies these effects and identifies time-related feedback mechanisms, providing insights into sustainability-oriented trade and industrial policies. PCA further confirms a negative correlation between sustainability scores and emissions. Policy recommendations emphasize renewable energy investments for ICT infrastructure, green technology promotion, digital literacy initiatives, and sustainable macroeconomic policies focused on resource optimization. These findings offer actionable strategies for Vietnam's Net Zero transition and provide valuable lessons for other emerging Asian economies facing similar challenges.